Pembinaan Belajar Membaca Melalui Media Kartu Huruf Abjad Peserta Didik - Najemia; Hardiyanti Ridwan; Irmayanti; Wahidayanti (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
The ability to read is one of the absolute abilities that must be owned by everyone. Reading ability that can be obtained from literacy is very important for elementary school children because literacy skills will affect their learning outcomes and their future. One of the important literacy for students is literacy literacy. Several students at SDN 09 Balang-Balang Sinjai Barata were not fluent in reading. One of the appropriate methods used is coaching using alphabet letter card media. The method used in this service is the coaching method using alphabetic card media. This coaching activity was carried out in Balakia Village, West Sinjai District, Sinjai Regency, especially at Balang-Balang 69 Elementary School for a month. The stages of coaching carried out are observation, implementation and evaluation. The results of coaching carried out using alphabet letter card media show that 100% of students who were previously not fluent in reading became fluent in reading, students know letters, spell words, read words, and read sentences and understand reading well